Enhancing University Students’ Listening Comprehension Using the TOEFL Learning English Application (MALL) : A Quantitative Study - Nuriza Johan, Andrea; Fitriati, Sri Wuli; Mujiyanto, Januarius Wuli; Widhiyanto, Widhiyanto Wuli (Journal of educational technology development and exchange, 2025)
This study investigates the effectiveness of the TOEFL Learning English Application in enhancing the listening comprehension skills of English as a Foreign Language (EFL) learners and explores students’ perceptions of its use. A descriptive quantitative design was employed involving 45 English Education students at Universitas Muhammadiyah Purworejo. Pre- and post-tests measured listening comprehension gains, while a questionnaire based on the Technology Acceptance Model assessed student perceptions. Results showed a statistically significant improvement in listening scores, as well as generally positive perceptions regarding the application’s accessibility, usability, and ability to reduce learning anxiety. These findings support using the TOEFL Learning English application as a beneficial tool for promoting flexible, autonomous, and engaging listening practice.